The Effect of Ratio of Beet and Pineapple Juice and Concentration of Sugar on Quality of Bitnas Syrup - Dyna Juniaty; Sentosa Ginting; Terip Karo-Karo (Universitas Sumatera Utara, 2015)
This research was to determine the effect of ratio of beet and pineapple juice and concentration of sugar on the quality of syrup. This research was conducted in September 2014 in Food Techonology Laboratory, Agriculture Faculty, North Sumatera, Medan. This research was using factorial Completely Randomized Design (CRD) with two factors, i.e :ratio of beet and pineapple juice (S)(70:30%, 60:40%, 50:50%, 40:60%, 30:70%) and concentration of sugar (G) (55%, 60%, 65%). The analyzed parameters were vitamin C content (mg/100 g sample), total soluble solid (oBrix), total acid (%), pH, viscosity (mpas), and organoleptic values (colour, aroma, and taste). The results showed that ratio beet and pineapple juice had highly significant effect on vitamin C content (mg/100 g sample), total soluble solid (oBrix), total acid (%), viscosity (mpas), and organoleptic values (colour, aroma, and taste). The concentration of sugar had highly significant effect on vitamin C content (mg/100 g sample),total soluble solid (oBrix), total acid (%), viscosity (mpas), and organoleptic value of taste. The interaction of the two factors had highly significant effect on organoleptic value of taste. The best treatment which gave the best effect on juice was 30:70% of beet and pineapple juice and 65% sugar. Keyword : concentration of sugar, juice, ratio of beet and pineapple juice